Kecanduan Internet Gaming dan Status Body Mass Index (BMI) Pada Remaja Tingkat Sekolah Menengah Pertama Tahun 2018 - M Arsyad Subu; Peni Rahmawati; Imam Waluyo; Rinto Agustino (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
The development of electronic media, especially gadgets that are increasingly sophisticated in recent years such as the use of the internet, playing games online or offline is a popular activity in teenagers. Generally teenagers make several reasons to use the internet or play games as entertainment, reduce emotions, escape from reality, seek challenges and happiness. This study was to determine the relationship between internet gaming addiction and body mass index in adolescents aged 12-15 years of junior high school at kramat jati district, east jakarta,2018. This research is a further analysis of previous study conducted two weeks in July 2018. Sample were 315 adolescent aged 12-15 years old in KramatJati, East Jakarta were include in this study. Internet Gaming Disorder Scale-Short Form (IGDS9-SF) were used to measure internet gaming addiction and measurement of Body Mass Index. From the result of research, adolescent with low internet gaming addiction 177 students (70.8%) and normal body mass index 126 students (50.4%), with the results of the correlation r = -0.036 and p = 0.566. The results of internet gaming addiction with body mass index in adolescent has a weak relationship, and inversely proportional.